2002
DOI: 10.1182/blood.v99.9.3163
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance therapy with alternate-day prednisone improves survival in multiple myeloma patients

Abstract: The role of maintenance therapy in multiple myeloma is controversial. Recent studies have shown an improvement in both progression-free and overall survival for patients receiving maintenance treatment with a combination of interferon and glucocorticoids, compared with interferon alone. The role of glucocorticoids alone as maintenance therapy has not been previously addressed. We compared alternate-day, oral prednisone at 2 different dose levels (10 mg versus 50 mg) for remission maintenance among previously u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
122
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(126 citation statements)
references
References 37 publications
1
122
0
2
Order By: Relevance
“…Berenson et al evaluated the use of prednisone at either 50 mg every other day or 10 mg every other day in patients who had responded to infusional vincristine, doxorubicin, and oral dexamethasone. 53 With a median followup of 53 months, no difference was noted in PFS or OS from the start of induction therapy, but from the time of randomization to the two prednisone arms both PFS and OS were significantly prolonged on the higher dose steroid arm, suggesting a benefit for prednisone. In contrast, dexamethasone was studied as a maintenance therapy in older patients after induction with either MP or MD, and compared with observation alone by Shustik et al 54 PFS was prolonged significantly with dexamethasone, but steroid maintenance did not result in an enhanced OS, casting doubt on this approach.…”
Section: Maintenance Therapymentioning
confidence: 99%
“…Berenson et al evaluated the use of prednisone at either 50 mg every other day or 10 mg every other day in patients who had responded to infusional vincristine, doxorubicin, and oral dexamethasone. 53 With a median followup of 53 months, no difference was noted in PFS or OS from the start of induction therapy, but from the time of randomization to the two prednisone arms both PFS and OS were significantly prolonged on the higher dose steroid arm, suggesting a benefit for prednisone. In contrast, dexamethasone was studied as a maintenance therapy in older patients after induction with either MP or MD, and compared with observation alone by Shustik et al 54 PFS was prolonged significantly with dexamethasone, but steroid maintenance did not result in an enhanced OS, casting doubt on this approach.…”
Section: Maintenance Therapymentioning
confidence: 99%
“…3 Corticosteroids in high doses were shown to prolong the duration of the maintenance phase, but results concerning overall survival (OS) were controversial. 4,5 Interferon α-2b (IFN) exerts direct anti-myeloma activity 6 but yielded inconsistent results when tested as maintenance treatment. Two meta-analyses, one on individual patient data 7 and another on published results, 8 showed a marginal but statistically significant gain in both maintenance duration and overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15]17 A randomized trial showed a significant PFS benefit in patients receiving maintenance with pharmacologic (50 mg every other day) vs physiologic doses of prednisone. 19 Maintenance with thalidomide-prednisone prolonged PFS, with conflicting OS results. 20,21 This study aims to compare the efficacy and safety of consolidation with CRD versus MEL200-ASCT, followed by maintenance with lenalidomide-prednisone versus lenalidomide alone, in NDMM patients eligible for transplantation.…”
Section: Text Word Count (Max 3000): 2999 Introductionmentioning
confidence: 99%